Design and fabrication of automatic vegetable slicer / Muhammad Eizuddin Hamzah Zulkifli - Zulkifli, Muhammad Eizuddin Hamzah (2023)
A fabrication of a vegetable slicer will be proposed to this project. The objective and main purpose is to help those small business owner or food catering industry that want to make massive output of sliced vegetable when doing cooking activities at their area. The vegetable slicer tools will be fabricated using stainless steel material. Some fabrication processes of the product like cutting process, grinding process and assembly process will proposed. Conclusion, it will help people especially small business owner, food catering industry, small stall at side road doing cooking work with less energy used and user friendly.